An update on the Pauwels classification. Issue 1 (December 2016) - Shen, Min; Wang, Chen; Chen, Hui; Rui, Yun-feng; Zhao, Song
Abstract Background Femoral neck fractures typically occur as a result of high-energy mechanisms among non-geriatric patients. Complications, including femoral neck shortening, non-union, and avascular necrosis, are relatively common after the internal fixation of this fracture pattern. These complications have serious effects on young patients. The Pauwels classification, which is the first biomechanical classification for femoral neck fractures, is still frequently used to determine and prescribe the appropriate treatment for femoral neck fractures. However, we lack a unified standard for measuring the Pauwels angle, which may make the classification unreliable. Understanding the relationship between the Pauwels classification and the complications arising from the internal fixation of femoral neck fractures is necessary. Meanwhile, a Pauwels type III femoral neck fracture among young adults, which involves a high shear load at the fracture site, is difficult to treat successfully. In addition, the recognized internal fixation for this fracture pattern remains uncertain. Main body This review aims to provide an update on the viewpoint on the Pauwels classification including the measurement of the Pauwels angle and to present evidence to prove the aforementioned relationship. Moreover, this article also discusses the optimal internal fixation for femoral neck fractures based on the Pauwels classification. Conclusion A unified standard of measurement should be established for the Pauwels classification, which is still frequently used in the literature and in determining appropriate treatment for femoral neck fractures, to achieve a credible classification. In addition, more randomized, multicentric, and prospective trials should be conducted in the future to clearly understand the relationship between the Pauwels classification and complications arising from the internal fixation of femoral neck fractures and, consequently, to explore ideal fixations for a Pauwels type III femoral neck fracture.